Anti-Helicobacter pylori vaccine: mith or reality? - Yu. P. Uspenskiy (Sankt-Peterburg : NIIÈM imeni Pastera, 2019)
Here we review the data on the current studies aimed at developing anti-Helicobacter pylori vaccines. Unfortunately, no vaccines recommended for use in human are available now, despite a more than 30-year history of their development and a great body of evidence on vaccine efficiency in animals. Mechanisms underlying vaccine-related effects in animals and human are poorly determined and expect to be further clarified. Moreover, side effects related to vaccines have not investigated in detail. A long-lasting stay of H. pylori in the gastric lumen restricts potential protective effects of host cellular immunity (an effect is mainly associated with antibodies and antimicrobial peptides), that results in low efficacy of systemic immunization and weak immune response. In addition, further complications in developing natural and artificial (vaccination) immune response may be due to the high pathogen variability and low immunogenicity of related antigens. A choice of antigen is crucial upon generating any vaccine. The data on the main pathogen-derived antigens is of high importance while generating both mono- and multicomponent H. pylori vaccines. A number of various antigens was proposed for immunization against H. pylori, some of which are involved in the pathogenetic mechanisms of Helicobacter pylori infection: VacA, CagA, NapA, BabA, SabA and urease. Such vaccines turned out to be efficient in preventing experimental infection in animals. The use of purified microbial antigens successfully induces protective mechanisms to fight against infection, as demonstrated in animal studies (preventive and therapeutic protocols). Compared to using a single antigen, an association of two or three antigens can trigger stronger immune response. Currently, bacterial urease is considered as the most promising candidate antigen, which has been proved to be a valuable a vaccine antigen in numerous studies with mice, ferrets and primates. It remains unclear which route of administration for Helicobacter pylori vaccine would be superior compared to the remainder. Comparing various routes of vaccine administration demonstrated that that mice immunized intranasally and intrarectally resulted in markedly higher protection against Helicobacter pylori infection compared to oral vaccination. Development of H. pylori vaccine faced substantial obstacles due to the pathophysiological, immunological and technological challenges noted above, still remaining an issue so far. At present, a promising approach in advancing H. pylori vaccines is based on using mucosal adjuvants and generation of recombinant probiotics expressing H. pylori-derived antigens for triggering specific immune response upon vaccination.